Mass(ively) Effect(ive): Emotional Connections, Choice, and Humanity - Ward, Natalie M. (Eludamos: Journal for Computer Game Culture, 2008)
A brief review of Bioware's successful sci-fi game Mass Effect, a combination first person shooter and role playing game.